210 Integrated safety profile of atacicept from all clinical studies to date. (April 2019) - Gordon, Caroline; Bassi, Roberto; Chang, Peter; H Kao, Amy; Jayne, David; Wofsy, David; Ona, Victor; Fleuranceau-Morel, Patricia
Abstract : Background: We conducted an integrated analysis of pooled safety data from all 17 atacicept clinical studies across multiple indications to date, to characterize the safety profile of atacicept. Methods: Analyses were based on 3 pooled datasets: double-blind placebo-controlled (DBPC) set (n=1568; key endpoint: treatment-emergent AEs [TEAEs]); SLE set (n=761; key endpoint: IgG change and serious infection rates); and full analysis set (n=1845; key endpoint: exposure-adjusted mortality). Results: Of 1568 patients in the DBPC set, 30.8% received placebo, 8.2% atacicept 25 mg, 24.5% atacicept 75 mg and 36.5% atacicept 150 mg. Overall, baseline characteristics were balanced across treatment arms. Treatment exposure was similar with placebo and atacicept 75 and 150 mg (278.3, 225.0 and 286.7 patient-years, respectively), but was lower with atacicept 25 mg (51.5 patient-years). Exposure-adjusted TEAE rates were generally higher with atacicept vs placebo, with no consistent association between atacicept dose and cardiac arrhythmias, serious and severe infections or injection site reactions (table 1 ). Serious infection and serious TEAE rates were similar between atacicept and placebo. TEAE-related discontinuation rates were higher with atacicept vs placebo (16.1 vs 10.9 per 100 patient-years). In the SLE set, there was no association between reduced IgG levels and increased infection rates. Across all studies (full analysis set), 11 patients died during treatment (10 atacicept [0.5%], 1 placebo [0.1%]). Infection-related deaths in the DBPC set are shown in the table 1 . Exposure-adjusted mortality rates per 100 patient-years were 3.60 (95% CI: 0.90–14.38) with atacicept 25 mg, 0.34 (95% CI: 0.05–2.43) with 75 mg, 1.18 (95% CI: 0.49–2.82) with 150 mg, and 0.44 (95% CI: 0.06–3.12) with placebo. Conclusions: Results from this pooled analysis clarify the benefit-risk relationship for atacicept, which is being further evaluated in additional clinical studies in IgA nephropathy and SLE. Funding Source(s): Merck KGaA, Darmstadt, Germany